Field reports, Fall 1985 - Dinsmore, James J.et al (1985)
An annotated list of birds sighted by Jim Dinsmore and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1985. Epson - sheet feed